Cultural and educational potential of club activities in the 21st century as a pedagogical phenomenon - Aleksandr Vladlenovich Kamenets; Irina Aleksandrovna Urmina; Nina Alexandrovna Oparina; Galina Ivanovna Gribkova; Olga Lvovna Kosiborod (Revista on line de Política e Gestão Educacional)
The study reveals the main prospects and opportunities for club activities of cultural and educational orientation. The main prerequisites for the implementation of the cultural and educational potential of the club in the 21st century and the following areas of work with the population are analyzed. A shift in the main emphasis in the organization of club leisure in the direction of solving the main social problems of the individual and society by means of cultural and educational activities is proposed and substantiated. The authors identify the uniqueness of a modern club as a cultural and educational institution in the modern system of cultural services for the population. The proposed structural and functional analysis of club practice allows identifying new prospects for the development of a club as a social institution, where the potential of cultural and educational activities is used for strengthening and preserving the physical, social and mental well-being of a person as a national task.